Positive selection in extra cellular domains in the diversification of Strigamia maritima chemoreceptors - Almeida, Francisca C.; Sanchez-Gracia, Alejandro; Walden, Kimberly K.; Robertson, Hugh M.; Rozas, Julio (Frontiers in Ecology and Evolution, 2015)
The recent publication of a centipede (Strigamia maritima) genome has revealed that most members of the chemosensory gene families of ionotropic (IR) and gustatory (GR) receptors do not have identifiable orthologs in insect species. In other words, the diversity of these chemoreceptors in centipedes appears to have evolved after its split from other arthropod lineages. Here we investigate the role of adaptive evolution in S. maritima chemoreceptor diversification using an approach that allows us to discuss functional aspects of such diversification. We applied codon substitution models in a phylogenetic framework to obtain the distribution of selective constraints across the different domains in the IR and GR proteins, and to assess the impact of positive selection in the evolution of these chemoreceptors. We found low selective constraints in most IR and GR duplicates and significant evidence for the presence of positively selected amino acids in 2 of the 4 IR, and in 6 of the GR recent specific expansions. Mapping the sites with high posterior probability of positive selection in protein structure revealed a remarkable uneven distribution of fast-evolving sites across protein domains. Most of these sites are located in extracellular fragments of these receptors, which likely participate in ligand recognition. We hypothesize that adaptive evolution in ligand-binding domains was a major force driving the functional diversification of centipede chemoreceptors.